Acute Toxicity Study of the Leaf and Fruit Extracts of Avicennia marina (Forssk.) on Wistar White Male Mice - Duryat Duryat; Rodiani Rodiani; Tri Maryono (Pandawa Institute, 2025)
Avicennia marina has at least 36 types of flavonoid compounds that are potential anti-fertility agents. The study's objectives were to obtain safe doses and assess the potential risks of using A. marina extract. Toxicity testing was conducted on Wistar rats with doses of 0, 250, 500, 1000, 2000, and 4000 mg/kg BW for leaf and fruit extracts. Observations were made to measure the level of mortality and damage to important organs (liver, kidneys, and testes) both macroscopically and microscopically. Macroscopic observation included identifying changes in shape, color, and size. Microscopic observation was done to observe organ damage through histopathological tests. Results of the study show that the administration of A. marina extract, both leaf and fruit, resulted in a 100 % survival rate at all doses given and the LD50 >8 g/kg BW. Both leaf and fruit extracts of A. marina also did not cause a decrease in the size of the kidneys and testes, but at high doses, they potentially reduced liver size. These findings indicate that using A. marina extract at recommended doses is safe. Both leaf and fruit extracts of A. marina, at a dose of 250 mg/kg BW, did not cause negative effects on the major organs (liver, kidneys, and testes) of mice. This finding suggests that using A. marina extract at 250 mg/kg BW is safe for long-term use. Administration of A. marina extract at doses up to 500 mg/kg BW did not cause liver damage in mice, but it potentially caused mild kidney damage. This finding indicates that leaf and fruit extracts of A. marina still have the potential to be used as drug candidates but with dosage regulation below 500 mg/kg BW. Administration of leaf and fruit extracts at doses of 500, 1000, and 2000 mg/kg BW has been shown to reduce the fertility of mouse sperm cells by up to 30%. This finding indicates that A. marina has the potential to be a promising, safe herbal anti-fertility agent.